Seismic vulnerability assessment of existing masonry buildings: case study of the old city centre of Faro, Portugal - Vicente, Romeu (2014)
The seismic vulnerability and risk assessment of old city centre areas is truly essential in urban rehabilitation programs and should not be focused exclusively over recognized historical and patrimonial valuable buildings but also in relation to current old masonry buildings that are highly valued in urban context. In addition, due to their geographical, demographic or historical features some old city centres are particularly interesting and critical, in respect to seismic risk mitigation. An excellent example of this reality is the old city of Faro, Capital of the Algarve, Portugal, which is one of the most popular summer touristic destination in Europe in a prone seismic region. This fact explains the high seasonal flux of population, which together with the moderate to high seismic hazard of the Algarve region and a vulnerable building stock increases both the seismic and tsunami risk in this area. From the exposed, this paper approaches the seismic vulnerability assessment of old building stock through the application of a simplified vulnerability method to the old city centre of Faro. Such method is based on a vulnerability index, which can be used to evaluate physical damage and to create human and economic loss scenarios in a broad sense (Vicente et al., 2011). 191 buildings were evaluated in accordance with the referred methodology and the results obtained were subsequently integrated into a Geographical Information System (GIS) tool, which allows the spatial analysis of results (Ferreira et al., 2013).This tool constitutes a very valuable instrument for city councils and regional authorities, whom can decide in a faster and more accurate way the best risk mitigation strategies to follow at the urban scale.